2005
DOI: 10.1128/jvi.79.6.3713-3727.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Intracellular Localization of the Epstein-Barr Virus Protein BFLF2: Interactions with BFRF1 and with the Nuclear Lamina

Abstract: . 79:3703-3712). Here we describe the characterization of the product of the EBV BFLF2 gene, which belongs to a family of conserved herpesviral genes which include the UL31 genes of herpes simplex virus and of pseudorabies virus and whose products are known to interact with UL34, the positional homolog of BFRF1. BFLF2 is an early transcript and is expressed in a variety of cell lines upon EBV lytic cycle activation. Western blotting of purified virion preparations showed that BFLF2 is a component of intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 49 publications
10
135
0
Order By: Relevance
“…Alterations of the nuclear envelope have also been observed after coexpression of pUL31 and pUL34 homologs of EpsteinBarr virus (18). However, they did not include formation of perinuclear vesicles but rather presented as reduplications of the nuclear membrane.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Alterations of the nuclear envelope have also been observed after coexpression of pUL31 and pUL34 homologs of EpsteinBarr virus (18). However, they did not include formation of perinuclear vesicles but rather presented as reduplications of the nuclear membrane.…”
Section: Discussionmentioning
confidence: 79%
“…Both proteins interact, and formation of the pUL34/pUL31 complex is required for proper positioning of both complex partners, local dissolution of the nuclear lamina, modification of the host cell chromatin, and efficient release of nucleocapsids from the nucleus (14-21). pUL31 and pUL34 bind nuclear lamins A/C and B (15,18,20) and are required for recruitment of cellular protein kinase C (PKC). Phosphorylation of lamins presumably leads to local dissolution of the lamina (12,21).…”
mentioning
confidence: 99%
“…It is reported that synonymous codon usage bias may be connected with different biological factors (6,(10)(11)(12)(13). Further analysis found that synonymous codon usage pattern changed at distinct sites along a coding sequence (14), balances of strong versus weak base pair bonding (15,16), maintenance of DNA and RNA secondary structure (17), and translational efficiency and fidelity (6). Aujeszky's disease, which is provoked by the pathogenic factor of Pseudorabies virus (PRV) (also known as Suid herpesvirus 1,, is a regularly lethal disease with a global distribution that influences swine, mainly and other domestic and wild animals incidentally (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In EBV, the pUL34 positional homolog BFRF1 and the pUL31 positional homolog BFLF2 also interact with each other. HSV-1 UL34 or EBV BFRF1 mutant viruses showed a phenotype of nuclear retention (Lake and HuttFletcher, 2004;Farina et al, 2005;Gonnella et al, 2005;Calderwood et al, 2007). EBV BFLF2 functions in both viral DNA packaging and primary envelopment, as deletion of BFLF2 led to sequestration of nucleocapsids in the nucleus and production of more empty capsids without viral genomes (Granato et al, 2008).…”
Section: Primary Envelopment and Deenvelopmentmentioning
confidence: 99%